PENENTUAN QUALITY CONTROL (QC) RESOLUSI SPASIAL PADA CITRA CT SCAN DENGAN METODE LINE SPREAD FUNCTION (LSF) DAN POINT SPREAD FUNCTION (PSF) MENGGUNAKAN PHANTOM AAPM CT PERFORMANCE - Yusanti, Weirna; Budi, Wahyu Setia; Adi, Kusworo (BERKALA FISIKA, 2014)
Computed Tomography (CT scan) is one of the X-ray modalities used in radiodiagnostic, as result it needs to do Quality Control (QC). This study focused on the image quality test of CT Scan by considering the spatial resolution parameters and using calculation method of the digital image. The effect of exposure factors (voltage and electric current) was also on image quality. This study using multislice CT (MSCT) 128 slice and AAPM CT Performance Phantom. Phantom scanned with the variation of exposure factors (80, 100, 120 kV and 50, 100, 150, 200, 250, 300, 350, 400, 450, 500 mA). The determination of spatial resolution value derived from the value of Full Width at Half Maximum (FWHM) of the Line Spread Function (LSF) and Point Spread Function (PSF) graphics. Results shown that the higher voltage applied, the smaller value of FWHM which show better image quality. This method is able to detect spatial resolution up to the 5th level (hole diameter 0.75 mm), whereas it is only up to 3rd level (1.25 mm) visually. The image quality in this study has been compared with the rules of West Austr Compliance Testing Protocol 2006, and it is proved that theÂ image quality is still good, thus the CT Scanner is still feasible toÂ use. Key words: CT Scan, Spatial Resolution, Line Spread Function, Point Spread Function